Approaches to Assessing Knowledge Level of Business-Organization - S. N Kukushkin; O. E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article assesses the level of knowledge of business - organization with regard to transformation processes taking place in conditions of new economy development. Key stages of business-organization evolution were studied: pre-industrial, industrial and post-industrial, as well as the transition period to economy of knowledge. Specific features of creating and exchanging knowledge at each of the mentioned stages were shown. A model of organization in economy of knowledge was put forward, whose distinguishing feature is priority of organizational culture, knowledge and intangible factors, flexible specialization, relevant management and innovation character of all business-processes, as well as implementation of two key goals: maximum satisfaction of customer needs and development of personal abilities. The authors substantiate specificity of knowledge with regard to its dubious nature and propose methodological approach to assessment of the organization level of knowledge, which is based on analysis of 16 indicators combined in 4 groups: dynamics of business-organization development, system of education and training of personnel, scientific and technical and innovation potential, information system and information support of business-organization. In conclusion algorithm of estimating the index of knowledge level is described and advantages of this method are demonstrated.